STATINS CAN CAUSE MYASTHENIA GRAVIS: FACT OR FICTION?. Issue 11 (9th October 2013) - Virgo, Jonathan; Wong, Sui; Rantell, Khadija; Plant, Gordon
Abstract : Background: Case reports suggest a causal link between statins and myasthenia gravis (MG). Aims: To assess the risk of MG onset and worsening with statin therapy. Methods: (1) Retrospective case notes review (2) Linked case–control study. Results: 106 patients with MG were studied (56M:50F; mean age at onset 48.8 years ranging 13.4–84.8 years). Eighteen (17.0%) were using a statin at the time of disease onset; however, no cases were temporally associated with starting statin therapy (average time from starting statin to MG onset 5.25 years ranging 2.0–10.3 years). Mean length of follow–up was 7.8 years. Three out of twelve (25.0%) patients who started taking a statin after onset of MG experienced a prompt (within four weeks) worsening of symptoms. In the case–control study, 84 consecutive non–myasthenic patients (25M:59F; mean age at first appointment 43.9 years ranging 17.7–84.1 years) attending Neuro–Ophthalmology clinics were compared with the above 106 cases. Seven controls (8.3%) were taking a statin at the time of their first appointment. Logistic regression analysis (controlling for age differences) did not show a significant association between statin usage and MG onset (OR 1.70; p–value 0.32; 95% CI 0.60–4.87). When the same analysis was applied only to cases of late onset MG (≥40 years) and controls in the same age range, again no significant association was detected (OR 1.58; p–value 0.41; 95% CI 0.53–4.72). Discussion: This study supports the hypothesis that statins can aggravate MG. We observed a 25% rate of MG exacerbation in patients who started taking a statin after disease onset. This was higher than the value reported by Oh et al. 1 in a study on 170 patients with MG, where six out 54 (11%) patients given a statin promptly experienced an exacerbation. Neither this, nor our retrospective study identified any cases of statin–induced MG (defined as MG onset within 4 months of starting a statin). Our case–control study did not show a significant association between statin usage and MG onset. This is perhaps because statins do not cause MG; however, insufficient sample sizes may have precluded the detection of a weak causal association. Further research with larger sample sizes is required to support or disprove this hypothesis.